Clinical and Recent Patents Applications of PD-1/PD-L1 Targeting Immunotherapy in Cancer Treatment—Current Progress, Strategy, and Future Perspective - Guo, Libin; Wei, Ran; Lin, Yao; Kwok, Hang Fai (Frontiers in Immunology, 2020)
Targeting PD-L1 and PD-1 interactions is a relatively new therapeutic strategy used to treat cancer. Inhibitors of PD-1/PD-L1 include peptides, small molecule chemical compounds, and antibodies. Several approved antibodies targeting PD-1 or PD-L1 have been patented with good curative effect in various cancer types in clinical practices. While the current antibody therapy is facing development bottleneck, some companies have tried to develop PD-L1 companion tests to select patients with better diagnosis potential. Meanwhile, many companies have recently synthesized small molecule inhibitors of PD-1/PD-L1 interactions and focused on searching for novel biomarker to predict the efficacy of anti-PD-1/PD-L1 drugs. This review summarized clinical studies and patent applications related to PD-1/PD-L1 targeted therapy and also discussed progress in inhibitors of PD-1/PD-L1.